Management of Postgraduate Library of State Islamic Institute of Kediri in Increasing Students Reading Interest - Sri Ningsih (Didaktika Religia, 2019)
This article aims to examine how the management of the postgraduate library of State Islamic Institute of Kediri (IAIN Kediri) in increasing students reading interest. Technological developments have positive and negative values, especially in relation to reading interest and literacy culture. The convenience offered sometimes causes students’ reluctance to read printed books, which has been the main reference in every lecture. This article is written based on qualitative research in the form of case study, where the object of study, which is the center of discussion, is the IAIN Kediri postgraduate library. The results of the study show that the management of the Postgraduate Library of IAIN Kediri in increasing student-reading interest can be categorized into three forms. The first is to optimize services for the entire Postgraduate academic community, especially in an effort to facilitate the implementation of the Tri Dharma of Higher Education. The second is through layout settings, where it prioritizes the convenience of the academic community when doing activities in the library. Third is the diversification of collections, in which the form of library collections is not limited to collections in printed form but also granting broadest access to the academic community to explore non-printed collections such as journals and proceedings online.